Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 03, 1930 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1930)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 03. 1930. Petersburg was not taken that day nor the next. It did not fall until the very last days of the war. Grant entrenched and laid siege to it. Butler, hemmed into the Bermuda Hundred by Beauregard’s strategy was maneuvering to find a way out. Meanwhile, Hawley and his men lay behind their entrenchments waiting for developments and fuming over incompetent command.
1 electronic record. Scanned newspaper article. 2 image scans. 1.39 MB (1,468,348 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 41.4 MB (43,436,887 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers